Elesclomol induces copper‐dependent ferroptosis in colorectal cancer cells via degradation of ATP7A. Issue 12 (15th September 2021) - Gao, Wei; Huang, Zhao; Duan, Jiufei; Nice, Edouard C.; Lin, Jie; Huang, Canhua
Abstract : Cancer cells reprogram their copper metabolism to adapt to adverse microenvironments, such as oxidative stress. The copper chelator elesclomol has been reported to have considerable anticancer efficacy, but the underlying mechanisms remain largely unknown. In this study, we found that elesclomol‐mediated copper overload inhibits colorectal cancer (CRC) both in vitro and in vivo . Elesclomol alone promotes the degradation of the copper transporter copper‐transporting ATPase 1 (ATP7A), which retards the proliferation of CRC cells. This property distinguishes it from several other copper chelators. Combinational treatment of elesclomol and copper leads to copper retention within mitochondria due to ATP7A loss, leading to reactive oxygen species accumulation, which in turn promotes the degradation of SLC7A11, thus further enhancing oxidative stress and consequent ferroptosis in CRC cells. This effect accounts for the robust antitumour activity of elesclomol against CRC, which can be reversed by the administration of antioxidants and ferroptosis inhibitors, as well as the overexpression of ATP7A. In summary, our findings indicate that elesclomol‐induced copper chelation inhibits CRC by targeting ATP7A and regulating ferroptosis. Abstract : In this study, we describe the molecular mechanisms by which elesclomol‐mediated copper (Cu 2+ ) overload inhibits colorectal cancer (CRC) both in vitro and in vivo . Elesclomol elevated Cu 2+ levels in mitochondria and decreased the expression of the Cu 2+ transporter ATP7A, leading to Cu 2+ retention and the subsequent accumulation of reactive oxygen species. The process promoted the degradation of SLC7A11, which further enhanced oxidative stress and induced ferroptosis in CRC cells.